(untitled) (Revista Ciência Agronômica, 2019)
The aim of this study was to characterise genetic variability in five groups of Pseudoplatystoma reticulatum: Mato Grosso I (MT-I), Mato Grosso II (MT-II), Mato Grosso III (MT-III), Mato Grosso do Sul I (MS-I) and Mato Grosso do Sul II (MS-II), taken from a centre for genetic improvement. In order to determine the allelic frequency, observed heterozygosity (HO ), inbreeding coefficients (FIS), Hardy-Weinberg equilibrium (HW -p) and genetic differentiation, eight polymorphic microsatellite loci (Pcor01, Pcor05, Pcor08, Pcor10, Ppu01, Ppu04, Ppu09 and Ppu10) were selected, in which a total of 62 alleles were observed in the individuals (n = 211). The MS-I population had the highest (Pcor08 allele 83: 0.5000) and lowest (Pcor10 allele 50: 0.1667) mean values for allele frequency. Higher (HO = 0.782; 0.782) and lower (FIS = 0.034; 0.061) values were found in groups MS-I and MT-III respectively. The HW -p showed that the five groups presented deviations for most of the loci under analysis. Finally, genetic differentiation pointed to the formation of two large genetic groups, one formed by the groups from Mato Grosso and the other by the groups from Mato Grosso do Sul. These measurements can help selection in a breeding program and maintain genetic variability.